Legal regulation of the international financial centers – comparative analysis of international and Кazakhstani experience (Journal of actual problems of jurisprudence, 2022)
International financial centers (IFCs) became a driving force and an integral part of the modern global economics. Due to their vital importance in the attraction of the international investors, states are very interested in creating and developing their cities as an international financial center. Many researches have been conducted to analyze the IFCs and the factors contributing to its effectiveness, however, most of the studies have been made by the financial and economical scholars. So, the novelty of the given research is that it is done within the framework of juridical science, considering the aspects of legal regulation of the financial centers and those historical and modern legal methods which have been used to develop cities as financial centers. Our research suggests that there is a direct link between success of the city as a financial center and its effective legal regulation. So, our objective was to identify historical stages of the development of IFCs and distinguish its own unique method of legal regularization on the global scale as well as within Kazakhstan.Keywords: AIFC, RFCA, DIFC, special economic zone, special financial zone, legal regulation, constitutional regulation, patternless legal regulation, special legal regime.